Association between vitamin D receptor BsmI gene polymorphism and periodontitis: a meta-analysis in a single ethnic group - Cai, Ting; Yang, Zheng-Yan; Nie, Li; Zhen, Jia-Xiu; Deng, Li; Zhou, Zhi (Cellular and Molecular Biology, 2017)
Although many researchers have studied on the association between vitamin D receptor (VDR) BsmI polymorphism and periodontitis, this association remains elusive. To further assess the effects of VDR BsmI polymorphism on the risk of periodontitis, a meta-analysis was performed in a single ethnic group. We searched PubMed and Chinese databases for relevant studies till April 2017. The strength of the associations were assessed used pooled odds ratios (ORs) and 95% confidence intervals (CIs). Six studies including 757 periodontitis cases and 670 controls were identified at last. In the total analyses, VDR BsmI polymorphism was not associated with the risk of periodontitis in all models. The subgroup analyses suggested a significantly reduced risk of periodontitis in South China. In conclusion, our meta-analysis showed that VDR BsmI polymorphism was associated with the decreased risk of periodontitis in Chinese individuals from South China, and further studies in other ethic groups are required for definite conclusions.